Assessment of clinical, functional and radiological outcomes in patients with fracture of distal end radius managed with close reduction and internal fixation with multiple percutaneous K wires: a prospective, single centre study - Thaware, Ameya Dhuldeo; Garg, Rohit Nirbhay; Patil, Shailendra; Kuris, James (International Journal of Research in Orthopaedics, 2024)
Background: Distal end radius fractures are one of the commonest fractures, occurring in all the age groups. Different treatment modalities have been described in the literature ranging from conservative to operative including close/open reduction to external fixation. Our prospective study aimed at evaluating the outcomes and complications in these fractures managed by close means with multiple percutaneous K wires. Methods: All the patients with distal end radius fracture were treated with close reduction and internal fixation with multiple percutaneous K wires. They were then evaluated clinically with visual analogue scale (VAS) score, functionally with Mayo wrist score and radiologically with Sarmiento’s modification of Lindstrom’s criteria on the follow ups. Results: The study included a total of 152 patients (88 females and 64 males) with mean age being 49.5±10.4 years, with fall on outstretched hand being the most common mode of injury, and dorsal displacement (73.7%) being the most common X-ray finding. Maximum patients in the study had A2.2 fracture (80 patients) followed by C1.2 fracture type (36 patients). There was clinically and statistically significant improvement in the mean VAS scores on follow ups. Excellent functional and radiological outcomes were seen in 124 patients and 108 patients respectively. Conclusions: Close reduction and internal fixation with multiple percutaneous K wires is a cost effective and easy method to treat all distal end radius fractures, provided good anatomical reduction is achieved before the wires are put.